2008
DOI: 10.1002/tox.20432
|View full text |Cite
|
Sign up to set email alerts
|

The value of stress protein 70 as an environmental biomarker of fish health under field conditions

Abstract: Hsp70 protein in three tissue types (gill, liver, and muscle) from black bream (Acanthopagrus butcheri) collected in a highly variable estuarine environment was investigated to determine which tissue provides better intersite discrimination. The usefulness of hsp70 expression to identify anthropogenic stress under field conditions was evaluated. Intersite differences were detected in hsp70 levels in gill and white muscle of black bream while liver showed no spatial difference. There was high interfish variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 40 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…Certainly, circulating HSP70 changes with other physiological states, such as pregnancy, in humans and other animals (Molvarec et al 2010). HSP70 levels must thus be used with a battery of other stress markers due to high levels of interindividual and between-tissue variability in expression (Webb and Gagnon 2009;Gupta et al 2010;Morris et al 2013). Future studies should measure both constitutive and stress-induced HSP70 responses to different stressors in a range of tissues from seals of different ages, sexes, and species.…”
Section: Discussionmentioning
confidence: 97%
“…Certainly, circulating HSP70 changes with other physiological states, such as pregnancy, in humans and other animals (Molvarec et al 2010). HSP70 levels must thus be used with a battery of other stress markers due to high levels of interindividual and between-tissue variability in expression (Webb and Gagnon 2009;Gupta et al 2010;Morris et al 2013). Future studies should measure both constitutive and stress-induced HSP70 responses to different stressors in a range of tissues from seals of different ages, sexes, and species.…”
Section: Discussionmentioning
confidence: 97%
“…While evaluating the power of Hsp70 as an environmental biomarker of fish health under field conditions, Webb and Gagnon (2009) reported that Hsp70 measurement alone is less than sufficient to evaluate fish health conditions. The group argued that because of high variability between tissues and also between individuals, field measurements of Hsp70 should be complemented by evidence of changes in metabolic enzyme activity, DNA damage, and/or blood cortisol levels.…”
Section: Limitations Of Stress Genes In Toxicologymentioning
confidence: 98%
“…Recently several studies suggested that heat shock protein 70 (Hsp70) may serve as a potential biomarker for monitoring environmental pollutants (Scheil et al 2010;Webb and Gagnon 2009). Changes of Hsp70 gene expression in E. fetida were assessed after a 28-day exposure to AHTN and HHCB (Fig.…”
Section: Responses Of Stress Protein Gene Expressionmentioning
confidence: 99%